A multi-class model-based control scheme for reducing congestion and emissions in freeway networks by combining ramp metering and route guidance. (July 2017) - Pasquale, C.; Sacone, S.; Siri, S.; De Schutter, B.
Highlights: A multi-class control scheme for freeway traffic networks is proposed. It combines ramp metering and route guidance. It aims to reduce the total time spent and the total emissions in a balanced way. It is a feedback model-based predictive controller. Abstract: The paper proposes a multi-class control scheme for freeway traffic networks. This control scheme combines two control strategies, i.e. ramp metering and route guidance, in order to reduce the total time spent and the total emissions in a balanced way. In particular, the ramp metering and route guidance controllers are feedback predictive controllers, i.e. they compute the control actions not only on the basis of the measured system state, but also on the basis of the prediction of the system evolution, in terms of traffic conditions and traffic emissions. Another important feature of the controllers is that they have a multi-class nature: different classes of vehicles are considered and specific control actions are computed for each class. Since the controllers are based on a set of parameters that need to be tuned, the overall control framework also includes a module to properly determine the gains of the controllers. The simulation analysis reported in the paper shows the effectiveness of the proposed control framework and, in particular, the possibility of implementing control policies that are specific for each vehicle type.